The roles of entrepreneurial education: A mediation analysis between attitude and students’ entrepreneurial intention - Mat Nawi, Farahiyah Akmal; Baistaman, Julaina; Wan Mustapha, Wan Masnieza; Abu Bakar, Hatinah (Journal of Islamic, Social, Economics and Development, 2025)
Nowadays, it is acknowledged that entrepreneurship plays a significant role in fostering innovation, productivity, job creation, and social and economic advancement. This study investigates the mediating role of Entrepreneurial Education in the relationship between Attitude and Entrepreneurial Intention among university students. While prior research has frequently highlighted the importance of both psychological factors and educational exposure in predicting entrepreneurial outcomes, findings remain mixed regarding the actual contribution of formal entrepreneurship education. Using Partial Least Squares Structural Equation Modelling (PLS-SEM), data from a structured questionnaire were analyzed to test the direct and indirect effects among the constructs. The results revealed that Attitude has a strong and significant direct effect on Entrepreneurial Intention (β = 0.817). However, Entrepreneurial Education did not mediate this relationship as expected. These findings suggest that students with a favourable attitude toward entrepreneurship are likely to develop strong entrepreneurial intentions regardless of their exposure to entrepreneurial education. The study provides theoretical contributions to the entrepreneurial intention literature by challenging the assumption that Entrepreneurial Education always enhances entrepreneurial motivation. Practically, the results highlight the need for universities to re-evaluate how entrepreneurship is taught and to design more experiential and attitude-aligned programs. Future research should explore other potential mediators and examine the long-term impact of education on actual entrepreneurial behavior.